Language proficiency is only part of the story: Lexical access in heritage and non-heritage bilinguals. (October 2021) - Wiener, Seth; Tokowicz, Natasha
This study examined how language proficiency and age of acquisition affect a bilingual language user's reliance on the dominant language during lexical access. Two bilingual groups performed a translation recognition task: Mandarin–English classroom bilinguals who acquired their dominant language (Mandarin) from birth and their non-dominant language (English) post-puberty through formal classroom instruction, and Mandarin–English heritage bilinguals who acquired their non-dominant language (Mandarin) at home from birth but became more dominant in another language (English) through society and peers. Participants decided whether word pairs were correct translations as quickly and accurately as possible. Critical trials involved correct translations (e.g. 房东 – landlord) and incorrect translations that were related to the correct translation in meaning (e.g. 房东 – rent) or form (e.g. 房东 – lantern). When identifying correct translations, lower proficiency heritage bilinguals were slower and less accurate than higher proficiency classroom bilinguals. Yet, when rejecting incorrect translations, heritage bilinguals demonstrated a greater magnitude of semantically-related interference than classroom bilinguals. Heritage bilinguals additionally demonstrated small but measurable amounts of form-related interference whereas the classroom bilinguals did not. Heritage bilinguals thus showed unique patterns of lexical access distinct from bilinguals who acquired their non-dominant language at a later age in a classroom setting.